2009
DOI: 10.1111/j.1758-2229.2008.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: a catalyst for global expansion of harmful cyanobacterial blooms

Abstract: Cyanobacteria are the Earth's oldest known oxygen-evolving photosynthetic microorganisms, and they have had major impacts on shaping our current atmosphere and biosphere. Their long evolutionary history has enabled cyanobacteria to develop survival strategies and persist as important primary producers during numerous geochemical and climatic changes that have taken place on Earth during the past 3.5 billion years. Today, some cyanobacterial species form massive surface growths or 'blooms' that produce toxins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
808
3
24

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,326 publications
(916 citation statements)
references
References 87 publications
27
808
3
24
Order By: Relevance
“…As the global climate changes, the occurrence and intensity of toxic cyanobacterial blooms are expected to increase (Paerl and Huisman, 2009;Michalak et al, 2013 Paerl andOtten, 2013). Direct effects, such as rising temperatures, and indirect effects, such as intensified stratification, favor cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%
“…As the global climate changes, the occurrence and intensity of toxic cyanobacterial blooms are expected to increase (Paerl and Huisman, 2009;Michalak et al, 2013 Paerl andOtten, 2013). Direct effects, such as rising temperatures, and indirect effects, such as intensified stratification, favor cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton blooms are a potential threat to the use of water, especially for drinking and irrigation water supply, fisheries and recreational purposes (Paerl and Huisman, 2009). For example, cyanobacteria can produce harmful toxins (Carmichael, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, cyanobacteria can produce harmful toxins (Carmichael, 1992). Furthermore, increasing nutrient loading, warming climate and growing CO2 emissions are likely to favour cyanobacterial expansion in a broad range of aquatic ecosystems (Paerl and Huisman, 2009). However, the effect of environmental change on phytoplankton blooms and its consequences on water quality has only been addressed recently for lakes (Elliott, 2012;Thackeray et al, 2008), and not yet tackled for river systems, except through some qualitative description of potential impacts by Arnell et al (2015), Johnson et al (2009) and Whitehead et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of cyanobacterial blooms involve the combined effects of physical (e.g., light, temperature, turbulence and mixing, and water residence time), chemical (e.g., nutrients, dissolved carbon, and salinity), and biological (e.g., grazing, microbial interactions, and allelopathy) factors and are also affected by the cyanobacterium itself (Dokulil and Teubner 2000;Heisler et al 2008;O'Neil et al 2012;Paerl and Otten 2013). Nutrients (particularly nitrogen and phosphorus) play vital roles in bloom formation (Håkanson et al 2007;Heisler et al 2008;Paerl et al 2014), and meteorological factors, climate change (Hu et al 2009;Paerl and Huisman 2008;Verspagen et al 2014;Zhang et al 2012), and their indirect effects (Callieri et al 2014;Paerl and Huisman 2009;Posch et al 2012) have also been identified as contributors to the expansion of cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%